Da natureza à cultura : tecnonatureza como novo paradigma ambiental - Santos Filho, Agripino Alexandre dos (2015)
The overall objective of this research is to propose a new environmental paradigm and the means for their enforcement. The specific objectives are: describe the concept of environmental paradigm; analyzing the structure and dynamics of modern environmental crisis; present another environmental paradigm based on the idea technonature; proposing the legal field as a means to overcome the systemic blockages that prevent the paradigmatic transition. It is a fundamental or theoretical research, which uses the method of hypotheticaldeductive approach, the method of historical-critical procedure and the procedure bibliographic data collection, having interdisciplinary character. The results allow us to infer that the modern environmental paradigm was efficient to better understand the functioning of natural processes to promote human welfare, but their hypertrophy led exhausted, making it unable to identify and resolve environmental problems affecting modern societies. However, the modern environmental crisis does not develop to the point of allowing a paradigmatic transition, because of the delaying structure, developed in late modernity, the stall indefinitely. The appropriate treatment is to build another environmental paradigm based on the idea technonature, as a synthesis between the natural and the cultural, surpassing the exhaustion of the modern environmental paradigm and redirecting social practices, with a view to rebuilding the civilization model under new bases. The legal field, in a democratic state, is a medium that allows establishing and securing new metasubjetivos rights, constituting a symbolic struggle for space where a new environmental paradigm can be said, breaking the systemic blockages.